Context-dependent functionality of 2′-fucosyllactose with Bifidobacterium breve M-16 V and short-chain galacto−/long-chain fructo-oligosaccharides in infant gut fermentation - Wenbo Guo; Binghui Zhou; Youlan An; Huiying Qiu; Lintao Zhang; Xianfeng Zhao; Xinyu Li; Bowen Shi; Ao Liu; Xiaoze Pang; Zhe Wang; Xinjie Zhu; et al. (Food Research International, 2026)

Systemic toxicity of thiamethoxam in the mud crab (Scylla paramamosain): Oxidative stress, neurotoxicity, and growth retardation - Zhennan Wang; Ye Sun; Kaiming Luo; Shaolin Yao; Ce Shi; Changkao Mu; Chunlin Wang; Pingping Zhan; Yangfang Ye (Environmental Pollution, 2026)

Bioinspired solar membrane distillation guttation leaf with enhanced salt resistance and uniform vapor flux - Lu Wang; Yanjie Zheng; Dian-ce Gao; Yong Jin; Yelin Zhang; Yongjun Sun (Desalination, 2026)

Physiological and multi-omics analyses reveal distinct effects of green light and increased silicate supply on cellular fucoxanthin content and fucoxanthin titer in Thalassiosira weissflogii - Ruibin Sun; Dongxu Li; Ce Liu; Mengzhen Cheng; Xu Gao; Zhanru Shao (Bioresource Technology, 2026)

All-in-one texture restoration of building Façade with generative diffusion prior - Xiaoan Liu; Xinyi Liu; Yongjun Zhang; Wanjie Sun; Ce Wang; Tingyun Li; Dongdong Yue (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Gelation properties and swallowing characteristics of chia seed gum/fish gelatin composite gels as dysphagia management - Peng-Yuan Sun; Lin Li; Bin Lai; Ce Wang; Jia-Nan Yan; Qian Zhang; Hai-Tao Wu (Food Chemistry, 2026)

Dynamic responses of an 18 MW floating offshore wind turbine under collinear and opposite wind-wave-current conditions: An experimental study - Zhijun Wei; Zixuan Wang; Xinyu Li; Jinlong Chen; Ce Sun (Ocean Engineering, 2026)

An experimental study on the ignition and combustion characteristics of ultrafine boron particles - Ruining He; Xin Bai; Xuan Ren; Yilin Zhao; Xin Wang; Jinhu Liang; Fei Qin; Ce Sun; Taufiq Yap Yun Hin; Chong-Wen Zhou; Henry J Curran; Yang Li (Fuel, 2026)

Dietary optimal arginine content of juvenile mud crab Scylla paramamosain and its roles in growth promotion and immune defense - Qiang Li; Zhennan Wang; Ye Sun; Mingming Niu; Ce Shi; Herve Migaud; Changkao Mu; Chunlin Wang; Yangfang Ye (Marine Life Science & Technology, 2026)

Breast-Milk Lactobacillus Gasseri FN136 Alleviates DSS-Induced Ulcerative Colitis Through Microbiota-Independent Metabolite–Host Interactions - Qingcui Li; Wenhao Wang; Fan Zhou; Xin Geng; Ce Qi; Chengwen Li; Jin Sun (Probiotics and Antimicrobial Proteins, 2026)

Detoxification and activation of municipal solid waste incineration fly ash through synergistic treatment with surfactants and Bacillus mucilaginosus: Process optimization and mechanistic analysis - Shaoming Sun; Ce Fang; Tongqian Guo; Aobo Yan; Lijuan Kong; Yazhou Liu; Yajian Wang (Fuel, 2026)

Identification of new isolates of Puccinia polysora and their interactions with RppC and RppK in maize - Huijin Sun; Xinxing Li; Yufan Wang; Xincao Li; Zixuan Wang; Huanying Li; Javed Hussian Sahito; Jihuan Tang; Ce Deng; Junqiang Ding (Physiological and Molecular Plant Pathology, 2026)

Corrigendum to “Construction of magnetically responsive xanthan gum hydrogels for tunable drug delivery” [Carbohydrate Polymers (2026) 124494] - Yao Sun; Tiantian Li; Jingjing Cao; Haotian Zhang; Ce Liang (Carbohydrate Polymers, 2026)

Design of a flexible cellulose framework via supramolecular structure modulation and its application in hydrogel sensors - Yantao Song; Minghui Yang; Tianhao Liu; Ce Sun; Min Jin; Haiyan Tan; Dingyuan Zheng; Yanhua Zhang (Carbohydrate Polymers, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Construction of magnetically responsive xanthan gum hydrogels for tunable drug delivery - Yao Sun; Tiantian Li; Jingjing Cao; Haotian Zhang; Ce Liang (Carbohydrate Polymers, 2026)

Towards probabilistic interpretations for the deterministic magnetic inversion: A case study of borate deposits of Liaoning province, Northeast China - Ce Yang; Changwei Qi; Bing Liu; Xiujing Tang; Guitao Sun; Xiaolong Wei; Yingqiang Yu; Baochun Li; Gaofeng Ye; Ji’en Dong (Applied Geophysics, 2025)

Asthenospheric upwelling-induced seismic activity in the eastern North China Craton: Evidence from viscosity obtained from an MT study - Baochun Li; Gaofeng Ye; Sheng Jin; Wenbo Wei; Letian Zhang; Hao Dong; Chengliang Xie; Yaotian Yin; Shaohuai Sun; Zhaoyuan Kang; Peng Ding; Yiwu Zhang; et al. (Tectonophysics, 2025)

Long-term evolution mechanisms of permeability during gas injection for enhanced coalbed methane recovery - Lei Yang; Chaojun Fan; Mingkun Luo; Quanle Zou; Ce Jia; Qiwang Sun; Zhiheng Cheng (International Journal of Rock Mechanics and Mining Sciences, 2025)

Limosilactobacillus reuteri FN041 alleviates cow's milk β-lactoglobulin–induced food allergy through immune modulation and gut microbiota remodeling - Renqiang Yu; Weijia Li; Zhou Zhou; Yue Yin; Zichen Luo; Ce Qi; Shanyu Jiang; Xiaoqing Chen; Danni Ye; Jin Sun (Food Bioscience, 2025)

Flexible fluorescent sensor based on a heterojunction-functionalized hydrogel with dual-mode crosslinking for H2S monitoring during fish spoilage - Zhixin Jia; Jingbin Zhang; Haocheng Fu; Zengtao Ji; Jiaran Zhang; Xinting Yang; Ce Shi; Xia Sun; Yemin Guo (Chemical Engineering Journal, 2025)

ALN-modified MnO2-x/PEEK implant for bone-targeted catalytic therapy in postoperative osteosarcoma repair - Miaomiao He; Ce Zhu; Dan Sun; Yueming Song; Ganjun Feng; Limin Liu; Li Zhang (Chemical Engineering Journal, 2025)

Balance between strength and toughness for fully bio-based composites achieved by oriented design of filler - Kang Chen; Ruixia Liu; Ce Sun; Dingyuan Zheng; Yuanyuan Miao; Yingfeng Zuo; Haiyan Tan; Yanhua Zhang (Chemical Engineering Journal, 2025)

Supplementing Limosilactobacillus reuteri FN041 alleviates hypercholesterolemia via promoting indole-3-carboxaldehyde production by gut microbiota in high-fat diet mice - Wenhao Wang; Qingcui Li; Xin Geng; Fan Zhou; Zhongya Wang; Yiying Wang; Xue Tang; Xiangrong Cheng; Jin Sun; Ce Qi (Food Bioscience, 2025)

Deformation Characteristics and Countermeasures of Roadway Surrounding Rock in Gas- and Water-Rich Coal Seam - Lei Yang; Chaojun Fan; Mingkun Luo; Hao Sun; Ce Jia; Lei Wang (Rock Mechanics and Rock Engineering, 2025)

Study of epiphytic non-geniculate coralline algae Reveals an Evolutionarily significant Genus, Pseudoderma gen. nov. (Lithophylloideae, Corallinophycidae) - Shu-Heng Yan; Xu-Lei Wang; Zhong-Min Sun; Bang-Mei Xia; Wen-Hui Gu; Guang-Ce Wang (Molecular Phylogenetics and Evolution, 2025)

Map-Assisted remote-sensing image compression at extremely low bitrates - Yixuan Ye; Ce Wang; Wanjie Sun; Zhenzhong Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Advancements in mechanisms and drug treatments for fibrodysplasia ossificans progressiva - Yijun Zhou; Ce Shi; Hongchen Sun (Journal of Zhejiang University-SCIENCE B, 2025)

Simultaneous regulation of interface chemistry and solvation structure by multifunctional organic salt anions for durable zinc anodes - Pengtao Wang; Kaifeng Yu; Tingting Jia; Haonan Wang; Jie Song; Zitian Sun; Xiaofeng Wang; Ce Liang (Chemical Engineering Journal, 2025)

Semantic guided large scale factor remote sensing image super-resolution with generative diffusion prior - Ce Wang; Wanjie Sun (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Encapsulation of melatonin in zein/pectin composite nanoparticles: Fabrication, characterization, and in vitro release property - Zhu-Jun Zhang; Wen Sun; Ce Wang; Bin Lai; Jia-Nan Yan; Hai-Tao Wu (Food Chemistry, 2025)

Bacterial dynamics and biotic sources in the developing swimming crab embryos - Ye Sun; Weichuan Lin; Qingyang Wu; Ce Shi; Chunlin Wang; Yangfang Ye (Aquaculture, 2025)

Detrital zircon provenance record of the northern shelf in the Rakhine Basin, Bay of Bengal - Liangbo Ding; Hongxia Ma; Guozhang Fan; Xiaoyong Xu; Hongping Wang; Guoping Zuo; Ying Zhang; Hui Sun; Jianan Wu; Junmin Jia; Ming Su; Ce Wang (Marine and Petroleum Geology, 2025)

Human milk-derived Limosilactobacillus reuteri FN041 ameliorates DSS-induced colitis by remodeling gut microbiota and metabolites in mice - Zichen Luo; Jin Sun; Ji Liu; Ping Yu; Danni Ye; Ce Qi; Xiaoqing Chen; Renqiang Yu (Food Bioscience, 2025)

Two-Dimensional Numerical Method for Predicting the Resistance of Ships in Pack Ice: Development and Validation - Yan Huang; Ce Sun; Jianqiao Sun (Journal of Marine Science and Engineering, 2024)
This study presents a 2D numerical simulation method for predicting the resistance of ships navigating in pack ice. The key contribution of this study lies in the derivation of analytical closed-form solutions for calculating the flexural deformation and stress distribution in an elastic plate using Symplectic Mechanics and Hooke’s laws. These solutions are used to determine the failure mode of ice floes. Linear Elastic Fracture Mechanics (LEFMs) and the weight function method are utilized to analyze crack initiation, propagation, and fracture. Ice is broken when a crack propagates to 14.5% of the ice length. The compressive strength of ice and the contact area are used to calculate the ice load. A collision method was developed based on the Sweep and Prune (SAP) and Gilbert–Johnson–Keerthi (GJK) algorithms. A program for predicting the resistance of ships navigating in pack ice was developed based on MATLAB and the aforementioned theories. The navigation resistance of RV Xuelong at different ice concentrations and speeds was simulated and compared with the model test results from an ice tank. The comparison shows that the simulation results are consistent with the test results, with an average error of 9.05%, indicating the effectiveness and reliability of this numerical method. This study lays a solid foundation for future research on autonomous ship navigation in pack ice.

Design strategy of super tough hydrophobic bamboo framework composites with internal network entanglement reinforcing structure - Guoying Liu; Junyue Shan; Lijun Cao; Hangqi Zhao; Ce Sun; Haiyan Tan; Yanhua Zhang (Chemical Engineering Journal, 2024)

Luteolin Protects against Vascular Calcification by Modulating SIRT1/CXCR4 Signaling Pathway and Promoting Autophagy - Xiaoyu Yu; Lei Xu; Ce Su; Changyuan Wang; Zimeng Wang; Yanna Wang; Xiaolong Lu; Huijun Sun (The AAPS Journal, 2024)

Remote sensing inversion of land surface temperature for cloud coverage areas based on NDVI in the North China Plain - Guofei Shang; Qixiang Yuan; Xia Zhang; Minghao Sun; Shizhuo Liu; Yongxiang Hu; Zhenghong Yan; Yuxin Gao; Ce Zhang (International Journal of Remote Sensing, 2024)

Impact of wind farms on local land surface temperature in Qinghai Province, China - Xia Zhang; Huimin Wang; Guofei Shang; Minghao Sun; Zhenghong Yan; Yuxin Gao; QiXiang Yuan; Ce Zhang (International Journal of Remote Sensing, 2024)

Evaluation of the biconditional transformation of land use: a case study of Minhou County in China - Minghao Sun; Guofei Shang; Xia Zhang; Jian Hua; Yongxiang Hu; Qingyue Hu; Zhenghong Yan; Ce Zhang; Yuxin Gao (International Journal of Remote Sensing, 2024)

Analysis of the space-time transformation of urban structure in Beijing-Tianjin-Hebei using NPP-VIIRS night-time light data - Minghao Sun; Guofei Shang; Xia Zhang; Zhenghong Yan; Yuxin Gao; Ce Zhang; Yubo Liu (International Journal of Remote Sensing, 2024)

Construction of amphoteric hydrogel electrolytes with charge modification: An investigation of ion migration mechanism and antibacterial property - Shao-Fei Sun; Xiao-Ya Zhao; Ce Gao; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2024)

Multi-dimensional microfluidic paper-based analytical devices (μPADs) for noninvasive testing: A review of structural design and applications - Ting Chen; Ce Sun; Syed Comail Abbas; Nur Alam; Sheng Qiang; Xiuzhi Tian; Chenglong Fu; Hui Zhang; Yuanyuan Xia; Liu Liu; Yonghao Ni; Xue Jiang (Analytica Chimica Acta, 2024)

Occurrence, distribution, and health risk assessment of pyrethroid and neonicotinoid insecticides in aquatic products of China - Manni Wu; Jingjing Miao; Wenhao Zhang; Qiaoqiao Wang; Ce Sun; Lu Wang; Luqing Pan (Science of The Total Environment, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Developing Prussian blue/wood-derived biochar catalyst for persistent organic pollutant degradation: Preparation, characterization, and mechanism - Dingyuan Zheng; Yuning Wang; Xiaoke Jia; Wenrui Yao; Shuo Wang; Zehuai Li; Ce Sun; Haiyan Tan; Yanhua Zhang (Chemosphere, 2024)

Environmental enrichment improves survival and growth of Portunus trituberculatus in recirculating aquaculture system by reducing energy expenditure and stress responses - Tianhan Xiong; Changkao Mu; Chunlin Wang; Peng Sun; Jie He; Ce Shi; Yangfang Ye (Aquaculture, 2024)

Telomere length as a modifier in the relationship between phthalate metabolites exposure and glucose homeostasis - Ruiqiang Li; Jiao Wang; Ying Wang; Xiaoyi Lin; Ce Sun; Lin Xu (Environmental Pollution, 2024)

Gel properties and interactions of hydrogels constructed with low acyl gellan gum and puerarin - Shi-Qi Xu; Yi-Nan Du; Zhu-Jun Zhang; Jia-Nan Yan; Jin-Jian Sun; Li-Chao Zhang; Ce Wang; Bin Lai; Hai-Tao Wu (Carbohydrate Polymers, 2024)

Synergistic reinforcement of polylactic acid/wood fiber composites by cellulase and reactive extrusion - Han Wan; Ce Sun; Chang Xu; Baiwang Wang; Yang Chen; Yueqiang Yang; Haiyan Tan; Yanhua Zhang (Journal of Cleaner Production, 2024)

A maleic anhydride-mediated green and sustainable route for versatile wood platform - Dingyuan Zheng; Zehuai Li; Wenrui Yao; Yuning Wang; Ce Sun; Haiyan Tan; Yanhua Zhang (Chemical Engineering Journal, 2024)

Effect of Proinflammatory S100A9 Protein on Migration and Proliferation of Microglial Cells - Qiao Bai; Dan Sun; Yang Zeng; Jie Zhu; Ce Zhang; Xiaoyin Zhang; Li Chen; Xin Zhou; Liu Ye; Yong Tang; Yonggang Liu; Ludmilla A. Morozova-Roche (Journal of Molecular Neuroscience, 2023)

Rheological properties of chia seed gum extracted by high-speed shearing and its comparison with commercial polysaccharides - Lin Li; Jia-Nan Yan; Bin Lai; Ce Wang; Jin-Jian Sun; Hai-Tao Wu (Food Hydrocolloids, 2023)

Ferritinophagy activation and sideroflexin1-dependent mitochondrial iron overload contribute to patulin-induced cardiac inflammation and fibrosis - Wen-Chang Sun; Ning-Ning Wang; Ru Li; Xian-Ce Sun; Jia-Wei Liao; Guang Yang; Shuang Liu (Science of The Total Environment, 2023)

Route Planning of a Polar Cruise Ship Based on the Experimental Prediction of Propulsion Performance in Ice - Yan Huang; Ce Sun; Jianqiao Sun; Zhipeng Song (Journal of Marine Science and Engineering, 2023)
The effective assessment of risk and speed limitations in ice are critical for the route planning of polar cruise ships. While the Polar Operational Limit Assessment Risk Indexing System (POLARIS) is widely used to evaluate the operational risk in ice, its scope of assessment is limited to the ship’s assigned ice class. For a specific ship with a given ice class, the propulsion performance under varying ice conditions is more essential for assessing the besetting risk and finding an optimal route. To establish a more detailed risk evaluation method for a PC6 class polar cruise ship, propulsion performance under various ice conditions is obtained via model tests in an ice tank. During the tests, the tow force, propeller torque, and thrust are measured under different ship velocities and propeller rotation rates, and the relations between required delivered power (P) and ship velocity (V) under the tested ice thicknesses and concentrations are obtained and extended to other ice conditions by curve fitting. A new risk index outcome, RIO*, is proposed after POLARIS according to the optimized load ranges of the ship’s rated power. Four risk levels, including low, medium, high, and unnavigable, are classified with the required propulsion power in ice being 50%, 85%, 100%, and >100% of the rated power, respectively. The recommended speed limit for each risk level is proposed based on the economical service speed of 11 kn, the operational limit of 3 kn by POLARIS and the minimum speed of 0.5 kn to avoid besetting, respectively. Based on the RIO* and P–V relations, the speed map for varying ice thicknesses and concentrations can be calculated. On these bases, a route planning simulation for the present polar cruise ship is performed. Results of the case study show that 29% of the simulated area is identified as “unnavigable” by the present procedure, while only 8% is detected by POLARIS.

Computer-vision-assisted subzone-level demand-controlled ventilation with fast occupancy adaptation for large open spaces towards balanced IAQ and energy performance - Zhitao Cui; Yongjun Sun; Dian-ce Gao; Jiaxin Ji; Wenke Zou (Building and Environment, 2023)

Kinetics of uptake and depuration of synthetic pyrethroid insecticides in manila clam (Ruditapes philippinarum) - Manni Wu; Xianming Tang; Ce Sun; Jingjing Miao; Qiaoqiao Wang; Luqing Pan (Environmental Science and Pollution Research, 2023)

Size-controllable Rh2P nanoparticles on reduced graphene oxide toward highly hydrogen production - Hongqiang Xin; Lan Sun; Yiwei Zhao; Yuanjiang Lv; Qiaomei Luo; Shengwu Guo; Danyang Li; Ce Mu; Bo Huang; Fei Ma (Chemical Engineering Journal, 2023)

Cobalt-loaded three-dimensional ordered Ta/N-doped TiO2 framework as conductive multi-functional host for lithium-sulfur battery - Ce Xu; Shaoning Zheng; Jing Guo; Daolai Sun; Zisheng Zhang; Jingde Li (Chemical Engineering Journal, 2023)

Nonlinear impacts of energy consumption and globalization on ecological footprint: Empirical research from BRICS countries - Qingru Sun; Ruxia Ma; Zenglei Xi; He Wang; Ce Jiang; Hanyu Chen (Journal of Cleaner Production, 2023)

A female in vivo haploid-induction system via mutagenesis of egg cell-specific peptidases - Xuecheng Zhang; Ce Shi; Siling Li; Bo Zhang; Pan Luo; Xiongbo Peng; Peng Zhao; Thomas Dresselhaus; Meng-Xiang Sun (Molecular Plant, 2023)

Disruption of phosphate metabolism and sterol transport-related genes conferring yeast resistance to vanillin and rapid ethanol production - Fengguang Zhao; Yaping Zhang; Jian Hu; Ce Shi; Xiang Ao; Shengding Wang; Ying Lin; Zhongwei Sun; Shuangyan Han (Bioresource Technology, 2023)

Correction: RNA m6A methylation promotes the formation of vasculogenic mimicry in hepatocellular carcinoma via Hippo pathway - Kailiang Qiao; Yantao Liu; Zheng Xu; Haohao Zhang; Heng Zhang; Chao Zhang; Zhi Chang; Xinyan Lu; Zhongwei Li; Ce Luo; Yanrong Liu; Cheng Yang; et al. (Angiogenesis, 2023)

Pyrethroids contamination and health risk assessment in seafood collected from the coast of Shandong, China - Manni Wu; Wenhao Zhang; Jingjing Miao; Ce Sun; Qiaoqiao Wang; Luqing Pan (Marine Pollution Bulletin, 2023)

Selective NO2 Detection by Black Phosphorus Gas Sensor Prepared via Aqueous Route for Ship Pollutant Monitoring - Yang Wang; Yujia Wang; Yue Sun; Kuanguang Zhang; Chenyang Zhang; Jianqiao Liu; Ce Fu; Junsheng Wang (Journal of Marine Science and Engineering, 2022)
The emission of nitrogen dioxide (NO2) caused by marine transportation has attracted worldwide environmental concerns. Two-dimensional (2D) black phosphorus (BP) is an emerging semiconductive material with the advantages of high electron mobility, a layer-dependent direct band gap and a large specific surface area. These properties ensure excellent potential in gas-sensing applications. In this work, BP quantum dots (QDs) are synthesized from commercial red phosphorus (RP) fine powder via the aqueous route. The BP QDs show uniform size distribution with an average size of 2.2 nm. They are employed to fabricate thin film gas sensors by aerial-assisted chemical vapor deposition. The microstructure, morphology and chemical composition are determined by various characterizations. The sensor performances are evaluated with the optimized response set to 100 ppm NO2 of 10.19 and a sensitivity of 0.48 is obtained. The gas sensor also demonstrates excellent repeatability, selectivity and stability. The fabricated thin film gas sensor assembled by BP QDs exhibits prospective applications in selective NO2 detection for marine gaseous pollutant monitoring and control.

Association of urinary or blood heavy metals and mortality from all causes, cardiovascular disease, and cancer in the general population: a systematic review and meta-analysis of cohort studies - Xianwei Guo; Wanying Su; Ning Li; Qiuxia Song; Hao Wang; Qiwei Liang; Yaru Li; Scott Lowe; Rachel Bentley; Zhen Zhou; Evelyn J. Song; Ce Cheng; et al. (Environmental Science and Pollution Research, 2022)

Influence of nitrate concentrations on EH40 steel corrosion affected by coexistence of Desulfovibrio desulfuricans and Pseudomonas aeruginosa bacteria - Zhihua Sun; Jiajia Wu; Dun Zhang; Ce Li; Liyang Zhu; Ee Li (Journal of Oceanology and Limnology, 2022)

RNA m6A methylation promotes the formation of vasculogenic mimicry in hepatocellular carcinoma via Hippo pathway - Kailiang Qiao; Yantao Liu; Zheng Xu; Haohao Zhang; Heng Zhang; Chao Zhang; Zhi Chang; Xinyan Lu; Zhongwei Li; Ce Luo; Yanrong Liu; Cheng Yang; et al. (Angiogenesis, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Tracing mantle sources in the northern Lau back-arc basin by independent component analysis of basalt isotopic compositions - Xichang Wu; Liyan Tian; Xuan-Ce Wang; Fengyou Chu; Quanshu Yan; Fengyue Sun; Xiaohu Li; Wei Wang; Luyao Yu; Zhenggang Li; Ling Chen (International Geology Review, 2020)

Proton pump inhibitors use and dementia risk: a meta-analysis of cohort studies - Yun Zhang; Mingming Liang; Chenyu Sun; Evelyn J. Song; Ce Cheng; Tingting Shi; Min Min; Yehuan Sun (European Journal of Clinical Pharmacology, 2020)

Isolation of living apical and basal cell lineages of early proembryos for transcriptome analysis - Xuemei Zhou; Ce Shi; Peng Zhao; Mengxiang Sun (Plant Reproduction, 2019)

Distinctive role of ACVR1 in dentin formation: requirement for dentin thickness in molars and prevention of osteodentin formation in incisors of mice - Xue Zhang; Ce Shi; Huan Zhao; Yijun Zhou; Yue Hu; Guangxing Yan; Cangwei Liu; Daowei Li; Xinqing Hao; Yuji Mishina; Qilin Liu; Hongchen Sun (Journal of Molecular Histology, 2019)

A two‐domain protein triggers heat shock pathway and necrosis pathway both in model plant and nematode - Lifang Ruan; Huihui Wang; Ge Cai; Donghai Peng; Hua Zhou; Jinshui Zheng; Lei Zhu; Xixi Wang; Haoquan Yu; Seng Li; Ce Geng; Ming Sun (Environmental Microbiology, 2015)
Summary The entomopathogen B acillus thuringiensis is equipped with multiple virulent factors. The genome sequence of B . thuringiensis YBT 1520 revealed the presence of a two‐domain protein named Nel which is composed of a necrosis‐inducing phytophthora protein 1‐like domain found in phytopathogens and a ricin B ‐like lectin domain. The merging of two distantly related domains is relatively rare. Nel induced necrosis and pathogen‐triggered immunity ( PTI ) on model plants. The Nel also exhibited inhibition activity to nematode. Microscopic observation showed that the toxicity of Nel to nematodes targets the intestine. Quantitative proteomics revealed that Nel stimulated the host defence. The Nel thus possesses dual roles, as both toxin and elicitor. Remarkably, the Nel protein triggered a similar response, induction of the heat shock pathway and the necrosis pathway, in both model plants and nematodes. The unusual ability of Nel to function across kingdom suggests a highly conserved mechanism in eukaryotes that predates the divergence of plants and animal. It is also speculated that the two‐domain protein is the result of horizontal gene transfer ( HGT) between phytopathogens and entomopathogens. Our results provide an example that HGT occurs between members of different species or even genera with lower frequency are particularly important for evolution of new bacterial pathogen lineages with new virulence. B acillus thuringiensis occupies the same ecological niches, plant and soil, as phytopathogens, providing the opportunity for gene exchange.

Retraction Note to: Meta-analysis of the relationship between single nucleotide polymorphism rs72689236 of caspase-3 and Kawasaki disease - Yanlin Xing; Hong Wang; Xiaomei Liu; Xianyi Yu; Rui Chen; Ce Wang; Xuexin Yu; Le Sun (Molecular Biology Reports, 2015)

Potential of Mesenchymal Stem Cells by Adenovirus-Mediated Erythropoietin Gene Therapy Approaches for Bone Defect - Chen Li; Jian Ding; Liming Jiang; Ce Shi; Shilei Ni; Han Jin; Daowei Li; Hongchen Sun (Cell Biochemistry and Biophysics, 2014)

RETRACTED ARTICLE: Meta-analysis of the relationship between single nucleotide polymorphism rs72689236 of caspase-3 and Kawasaki disease - Yanlin Xing; Hong Wang; Xiaomei Liu; Xianyi Yu; Rui Chen; Ce Wang; Xuexin Yu; Le Sun (Molecular Biology Reports, 2014)

Differentiation of Rabbit Bone Mesenchymal Stem Cells into Endothelial Cells In Vitro and Promotion of Defective Bone Regeneration In Vivo - Jinzhong Liu; Chao Liu; Bin Sun; Ce Shi; Chunyan Qiao; Xiaoliang Ke; Shutai Liu; Xia Liu; Hongchen Sun (Cell Biochemistry and Biophysics, 2014)

Effects of normalized difference vegetation index and related wavebands’ characteristics on detecting spatial heterogeneity using variogram-based analysis - Zhaofei Wen; Ce Zhang; Shuqing Zhang; Changhong Ding; Chunyue Liu; Xin Pan; Huapeng Li; Yan Sun (Chinese Geographical Science, 2012)

Biomechanism of adhesion in gecko setae - Ce Guo; JiuRong Sun; YingBin Ge; WenBo Wang; DaPeng Wang; ZhenDong Dai (Science China Life Sciences, 2012)

Effect of blue light on indoor seedling culture of Saccharina japonica (Phaeophyta) - Wen-Jun Wang; Xiu-Tao Sun; Guang-Ce Wang; Pu Xu; Xiang-Yu Wang; Zhe-Long Lin; Fei-Jiu Wang (Journal of Applied Phycology, 2010)